(untitled) (Al-Academy, 2025)
The role that posters play is one of vital effectiveness in developing environmental awareness through what visual communication media provide via advertisement designs and posters with expressive connotations about the subject of sustainability culture. These posters emphasize the presentation of topics directly connected to individuals’ lives and the sustainability of their resources. Thus, there is a functional aspect to these outputs upon which the designer determines the elements that suit the concept, as they achieve intellectual communication for the content of reading and understanding posters quickly and easily by the recipient. This prompted the researcher to investigate and research this subject, describing her research problem as follows: What is sustainability culture and its reflections in environmental posters designs? Meanwhile, the researcher defined the research objective as identifying sustainability culture and its reflections in environmental posters designs, which was included in the first chapter. The second chapter consisted of two sections: the first section (Sustainability Culture and Environmental Awareness in Posters designs) and the second section (Communication Process and Culture). The third chapter included the most important conclusions, which are: Sustainability culture was represented through presenting the design concept directly in posters to express the culture of countries،, which represents a point of connection and reinforcement of the country’s identity. The posters incorporated the employment of environmental cultural symbols inspired by the environmental reality of humans، in addition to formal and color symbols represented by a formal symbol for expressive connotation about the environmental recycling symbol in the image and text in posters.